Hutang Luar Negeri Dalam Perspektif Ekonomi Syariah - Kirom, Cihwanul (Sharia Faculty Islamic Economic Law Study Department, 2018)
The purpose of this study is to find out how foreign debt law is reviewed in terms of Islamic economics. Foreign debt is among the funding sources to meet the State expenditure budget. This foreign debt is very important, especially developing countries in improving the economy. However, this debt problem has become a long debate among the people. There are people who agree that if the country adds debt, there are also those who disagree about it. Especially in terms of the applicable aspects of sharia economic law, this study reveals various theories and laws on sharia economic perspective on foreign debt. The results of this study are hadith exposure and the level of debt budgeted by the government.